Pengaruh Rasio Profitabilitas, Leverage, dan Nilai Pasar Terhadap Harga Saham Bank Syariah yang terdaftar di Bursa Efek Indonesia Periode Juli 2021 - November 2022 - Prastiyani Prastiyani; Mochamad Reza Adiyanto (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
Financial Performance is one of the internal factors that influence the share price of Go Public companies. This study aims to determine the effect of financial performance on stock prices in Islamic banking companies listed on the Indonesia Stock Exchange (IDX) during the period July 2021 – November 2022. This research is a quantitative study. Sampling in this study used a purposive sampling technique in order to obtain 4 companies as research samples. The data used is taken from financial reports published by the IDX and websites of each company as well as stock prices obtained from Ksei.co.id. Data analysis using multiple linear regression data analysis. The results showed that partially the ROA and DER variables had a significant negative effect on stock prices. ROE and BVPS variables have a significant positive effect on stock prices. EPS variable has no effect on stock prices. Simultaneously ROA, ROE, DER, EPS, and BVPS affect the stock prices of Islamic banking companies listed on the IDX. The coefficient of determination (R2) in this study is 0.728, meaning that 72.8% of the variation of all independent variables (ROA, ROE, DER, EPS, BVPS) can explain the dependent variable (stock price), while the remaining 27.2% is explained by other variables not proposed in this study.